Germline Mutation in KIF1Bβ Gene Associated with Loss of Heterozygosity: Usefulness of Next-Generation Sequencing in the Genetic Screening of Patients with Pheochromocytoma. (30th May 2020) - De Filpo, Giuseppina; Contini, Elisa; Serio, Viola; Valeri, Andrea; Chetta, Massimiliano; Guasti, Daniele; Bani, Daniele; Mannelli, Massimo; Rapizzi, Elena; Luconi, Michaela; Maggi, Mario; Ercolino, Tonino; et al.
Abstract : The genetic approach of pheochromocytomas and paragangliomas has changed in the last two decades. Nowadays, we know that more than 40% of patients have a germline mutation in one of the susceptibility genes identified to date. Our aim is to underline how genetic diagnosis by next-generation sequencing (NGS) can improve the management of patients affected by pheochromocytomas and paragangliomas in our routine diagnostic screening. We reported a case presentation and next-generation sequencing analysis supported by in silico studies and evaluation of mitochondrial status in KIF1Bβ tissue. A 46-year-old male affected by a left secreting pheochromocytoma underwent surgery in 2017. After surgery, the normetanephrine levels decreased very slowly and a suspected abdominal lymph node was detected. We found a novel germline KIF1Bβ gene mutation, c.4052C > T, p. Pro1351Leu associated with tumor loss of heterozygosity, and resulted likely-pathogenetic by in silico studies. This mutation was also associated with an increased number of mitochondria through the electron microscopy compared with wild-type tissues as suggestive for mitochondria neoformation compensatory to the mitochondrial autophagic figures observed. Our results underline the usefulness of next-generation sequencing in the presence of multiple tumor predisposition genes and how, at the same time, its use may result challenging for the clinicians. To date, performing the genetic analysis according to the latest Consensus Statement is mandatory in patients affected by PHEO/PGL.